AR SINAPS: AUGMENTED REALITY LEARNING MEDIA TO ENHANCE CRITICAL THINKING ABILITY - Azrai, Eka Putri; Rini, Daniar Setyo; Kurnianto, Mathias Bagas; Ampang, Johsamer (International Journal of Education, 2023)
The competitive world situation caused by globalization requires students in the 21st century to have the ability to think critically. Critical thinking ability is a thinking process that has a purpose and focuses on producing an idea to solve a problem. However, several studies show that students' critical thinking skills in biology are still in the low to medium category. Thus, several efforts are needed to improve critical thinking skills, one of which can be through the use of technology-based learning media. This study aims to improve students' critical thinking ability using Augmented Reality learning media. This research was carried out from January to July 2022 at State Senior High School 31 Jakarta (henceforth called SMAN 31 Jakarta). The research used a quasi-experimental design with a pretest-posttest control group design. The experimental class used AR SINAPS learning media to assist the learning process. The control class, on the other hand, used picture media. The research involved 44 students selected by simple random sampling. The participants were divided into experimental and control classes, each of which amounted to 22 students. The data analysis technique used was a t-test with a significant level (α) = 0.05. Based on the calculations on the average gain score for the experimental and control classes, a significance value of 0.01 was obtained, meaning that using AR SINAPS learning media might enhance high school students' critical thinking ability better than using the picture media.